(untitled) (Journal of Fiber Bioengineering and Informatics, 2023)
The pomelo peel, a by-product of pomelo processing, is predominantly discarded. To fully exploit the pomelo peel resources and contribute to environmental improvement and resource recycling, this study reports a green method for extracting cellulose nanofibrils (CNFs) from pomelo peel through hydrothermal-assisted alkali treatment. Lemon juice is employed for further ball milling treatment to purify the CNFs. The chemical structure, crystallinity, thermal stability, and microstructure of pomelo peel powder and CNFs are analyzed. The study results demonstrate that the combination of alkali treatment, hydrothermal processing, bleaching, and ball milling progressively eliminates hemicellulose, lignin, and other impurities from the pomelo peel, yielding high-quality CNFs. The CNFs retain the natural cellulose structure, with enhanced thermal stability and crystallinity. The diameters of the CNFs range from 2-30 nm. This method employs lower NaOH concentrations than previous studies, resulting in CNFs with higher crystallinity and smaller diameters. This study provides a promising method for enhancing the value-added of pomelo peel and increasing the volume of CNF production.